Dental fear, anxiety, and phobia; causes, diagnostic criteria and the medical and social impact - Nadya Tsetsova Avramova (Journal of Mind and Medical Sciences)
Despite technological advances in modern medical science and practice, many people still associate dental treatment with unpleasant emotional sensations and pain. According to the current literature, dental fear and anxiety are psychological barriers that negatively affect frequency of patient attendance which results in avoidant behavior and poorer oral health-related quality of life.